Efficacy and Safety Analysis of Combination Therapy Consisting of Intravenous Immunoglobulin and Corticosteroids versus Respective Monotherapies in the Treatment of Relapsed ITP in Adults - Fang, Lijun; Sun, Jing; Zhao, Yongqiang; Hou, Ming; Wu, Depei; Chen, Yunfei; Yang, Renchi; Zhang, Lei (Global Medical Genetics, 2023)
Objective In this study, we aimed to evaluate the efficacy and safety of combination therapy, consisting of intravenous immunoglobulin (IVIg) and corticosteroids, in comparison to respective monotherapies in the treatment of relapsed immune thrombocytopenia (ITP) in adults.Methods A retrospective analysis of clinical data was conducted on 205 adult patients with relapsed ITP who received first-line combination therapy or monotherapy in multiple centers across China from January 2010 to December 2022. The study evaluated the patients' clinical characteristics, efficacy, and safety.Results We found that the proportion of patients with platelet counts in complete response was significantly higher in the combination group (71.83%) compared with the IVIg group (43.48%) and the corticosteroids group (23.08%). The mean PLTmax in the combination group (178 × 109/L) was significantly higher than that in the IVIg group (109 × 109/L) and the corticosteroids group (76 × 109/L). Additionally, the average time for platelet counts to reach 30 × 109/L, 50 × 109/L, and 100 × 109/L in the combination group was significantly shorter than in the monotherapy groups. The proportion curves for reaching these platelet counts during treatment were also significantly different from those in the monotherapy groups. However, there were no significant differences in the effective rate, clinical characteristics, and adverse events among the three groups.Conclusion We concluded that combining IVIg and corticosteroids was a more effective and faster treatment for relapsed ITP in adults than using either therapy alone. The findings of this study provided clinical evidence and reference for the use of first-line combination therapy in the treatment of relapsed ITP in adults.
Keywords: primary immune thrombocytopenia; adult relapse; first-line drugs; combination therapy